Identification of sarcopenic obesity in postmenopausal women : a cutoff proposal - Oliveira, Ricardo Jacó de (2011)
Sarcopenic obesity is the combination of reduced fat-free mass (FFM) and increased fat mass (FM) with advancing age but there is lack of clear criteria for its identification. The purposes of the present investigation were: 1) to determine the prevalence of postmenopausal women with reduced FFM relative to their FM and height, and 2) to examine whether there are associations between the proposed classification and health-related variables. A total of 607 women were included in this cross-sectional study and were separated into two subsets: 258 older women with a mean age of 66.8 ± 5.6 years and 349 young women aged 18-40 years (mean age, 29.0 ± 7.5 years). All volunteers underwent body composition assessment by dual-energy X-ray absorptiometry. The FFM index relative to FM and height was calculated and the cutoff value corresponded to two standard deviations below the mean of the young reference group. To examine the clinical significance of the classification, all older participants underwent measurements of quadriceps strength and cardiorespiratory fitness. Values were compared between those who were classified as low FFM or not, using an independent samples t-test and correlations were examined. The cutoff corresponded to a residual of -3.4 and generated a sarcopenic obesity prevalence of 19.8% that was associated with reduced muscle strength and aerobic fitness among the older participants. Also, the index correlated significantly with the health-related fitness variables. The results demonstrated reduced functional capacity for those below the proposed cutoff and suggested applicability of the approach as a definition for sarcopenic obesity.